Ecologia das comunidades de metazoários parasitos em peixes Clupeiformes (Actinopterygii) do litoral do Rio De Janeiro, Brasil - Luana Cristina da Silva Benicio (2024)
The Brazilian coastline is rich in water resources and extends for more than 8,500 km. Sepetiba Bay, located in the state of Rio de Janeiro, presents an important aquatic ecosystem for the country. In Brazil, the parasitic fauna of clupeid fish is little known, in addition, studies regarding the ecological aspects of parasites in these fish are generally restricted to one host species. Therefore, the present work evaluated, in a comparative way, the structure of metazoan parasite communities of 5 species of clupeid fish that are economically important, namely Brevoortia pectinata, Anchoa tricolor, Anchoa marinii, Harengula clupeola and B. aurea, for an ecological approach. wide and robust. For this, 100 specimens of B. pectinata were collected, which were subjected to parasitological analysis. Additionally, databases of parasite communities of A. tricolor (n = 103), A. marinii (n = 95), B. aurea (n = 42) and H. clupeola (n = 35) were obtained from the same locality. The fish were weighed, measured and differentiated according to sex. To characterize the parasite communities, population (prevalence, abundance and average abundance) and community descriptors (community status, dominance frequency, diversity by Brillouin index [HB] and richness) were estimated. Differences in prevalence and abundance per parasite species, diversity and richness of parasites between conspecific male and female hosts and between component parasite communities were analyzed. The similarity between parasitic communities was estimated qualitatively by the Jaccard index and quantitatively by the Bray-Curtis distance and subsequent cluster analysis and multidimensional spatial scaling. In order to evaluate whether the structure of the parasite community can be used to identify the host population, a canonical discriminant analysis was performed based on abundance and prevalence. Factor analyzes indicated the host species with greater dominance over parasitological indicators. The parasites presented an aggregated distribution, with few exceptions. The parasitic communities were mostly composed of adult stages, representing central and secondary species. In the ANOSIM results, it showed that the B. aurea community was closer to A. tricolor. However, NMDS tests and cluster analysis showed greater similarity between the B. Aurea and B. pectinata communities. The parasite communities in the present study were characterized by low diversity, low uniformity and high dominance. Most parasite taxa occurred in just one species of fish (specialists), and few parasites occurred in more than one host (generalist). In addition to providing the first parasitological data regarding B. pectinata, the present study contributed to the knowledge of parasite-host relationships in the region, providing important data for future studies.